Energetická náročnost přípravy teplé vody - Helánová, Blanka (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce na téma Energetická náročnost přípravy teplé vody se zabývá stanovením a porovnáním energetické náročnosti přípravy teplé vody v dvougeneračním rodinném domě s administrativní částí. Energetická náročnost přípravy teplé vody je stanovena dvěma výpočtovými metodami a experimentálním měřením, jež jsou v závěru porovnány. Výpočet je proveden podle normy ČSN 06 0320 a podle souboru norem ČSN EN 15316-3. Práce je zpracována v souladu s platnými legislativními předpisy.

Master’s thesis on Energy performance of domestic hot water preparation is concerned with calculating and comparing the energy performance of domestic hot water preparation in two-generation family house with an administrative part. Energy performance of domestic hot water preparation is calculated by two calculation methods and by experimental measurements, which are compared at the end of the thesis. The calculation is performed according to standard ČSN 06 0320 and set of standards ČSN EN 15316-3. Thesis is processed in accordance with valid legislative regulations.
Energy Performance of Domestic Hot Water Preparation
Keywords: Energetická náročnost přípravy teplé vody; teplá voda; potřeba teplé vody; potřeba tepla pro přípravu teplé vody; ztráty tepla; cirkulační okruh; zásobník teplé vody; tepelné čerpadlo; vstupní teplota vody; výstupní teplota vody (ze zásobníku).; Energy performance of domestic hot water preparation; domestic hot water; need of domestic hot water; energy need for domestic hot water; thermal loss; circulation loop; domestic hot water storage tank; heat pump; cold water inlet temperature; hot water outlet storage tank temperature.